High-dose vitamin D supplementation is related to an improvement in serum alkaline phosphatase in COVID-19 patients; a randomized double-blinded clinical trial - Reza Rezvani Moghaddam; Zahra Khorasanchi; Ayad Rasool Noor; MohammadReza Shadmand Foumani Moghadam; Ali Jafarzadeh Esfahani; Abdullah Khalaf Merhej Alyakobi; MohammedHadi Lafta Alboresha; Payam Sharifan; Ali Bahari; Reza Rezvani; Malihe Aghasizade; Maryam Heshmati; et al. (BMC, 2023)
Abstract Background The benefits and harms of vitamin D supplementation in the treatment of COVID-19 have not yet been fully documented. In this study, we aimed to evaluate the effects of high-dose vitamin D supplementation on liver function tests in COVID-19. Method This double-blinded randomized clinical trial was conducted on 140 hospitalized patients aged > 30 years. Patients were randomly allocated to receive either intervention group (n = 70 receiving 50,000 IU of vitamin D capsules orally as a single dose and then 10,000 IU syrup daily from the second day of admission for 30 days) and the control group (n = 70 receiving 1000 IU vitamin D syrup orally per day). Liver function tests (LFT), including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), and Lactate Dehydrogenase (LDH) were evaluated at baseline and at the end of the intervention. Decision tree analysis was performed to identify the predictors for change in liver enzymes. Results Among COVID-19 patients, a significant decrease was observed in serum level of ALP between intervention and placebo groups (p = 0.04). In addition, decision tree analysis revealed that GGT, temperature, serum magnesium level at baseline and gender were the most important predictors of ALT changes in COVID-19 patients. Conclusion High-dose vitamin D supplementation improved ALP markers among COVID-19 patients. More randomized controlled trials with longer follow-up times will be required.